2018
DOI: 10.1161/cir.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Cardiac Arrest Resuscitation Systems of Care: A Scientific Statement From the American Heart Association

Abstract: ABSTRACT:The American Heart Association previously recommended implementation of cardiac resuscitation systems of care that consist of interconnected community, emergency medical services, and hospital efforts to measure and improve the process of care and outcome for patients with cardiac arrest. In addition, the American Heart Association proposed a national process to develop and implement evidence-based guidelines for cardiac resuscitation systems of care. Significant experience has been gained with implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 140 publications
4
48
1
2
Order By: Relevance
“…Among EMS-treated patients with OHCA in 2015, 21.3% presented with an initial shockable rhythm [2]. Rapid access to defibrillation, therefore, is paramount to OHCAvictim survival with optimal neurological and functional outcomes [7]. Although the likelihood of survival is increased when by- standers witness, recognize, and respond to OHCA victims in a rapid manner, barriers to this full potential persist [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among EMS-treated patients with OHCA in 2015, 21.3% presented with an initial shockable rhythm [2]. Rapid access to defibrillation, therefore, is paramount to OHCAvictim survival with optimal neurological and functional outcomes [7]. Although the likelihood of survival is increased when by- standers witness, recognize, and respond to OHCA victims in a rapid manner, barriers to this full potential persist [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, cardiac resuscitation systems of care have been developed to increase bystander access to defibrillators [7]. In Denmark, Hansen and colleagues (2017) examined the association between AED placement and both by- stander defibrillator and survival rates after nationwide dissemination of AEDs, registration of AEDs with location linked to EMS dispatchers, dispatcher-guided use, and public education [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing systematic post-CPA care following the return of spontaneous circulation is very important for the prognosis of the CPA group when the initial rhythm is VF or pulseless ventricular tachycardia. TH contributes to improvements in neurological outcomes in patients after out-of-hospital CPA [24,25]. In general, candidates for TH after out-of-hospital CPA are expected to have a poor prognosis.…”
Section: Differences In Clinical Outcomesmentioning
confidence: 99%
“…Recent studies have demonstrated that up to a quarter of life-threatening situations, such as airway obstruction, severe dyspnoea, hemodynamic instability and abnormal Glasgow Coma Scale, require TCHI [8][9][10]. As proposed by the American Heart Association and the American Stroke Association since 2013, acute ST-elevation myocardial infarction (STEMI), suspicion of acute stroke and out-of-hospital cardiac arrest (OHCA) require rapid transportation from the field (fast-track) to benefit from an urgent procedure and therefore also may be considered as TCHI [16][17][18].…”
Section: Introductionmentioning
confidence: 99%